Evaluasi Kebocoran Tepi Bonding Generasi V dan Bonding Generasi VII Pada Restorasi Kelas V Resin Komposit Microhybrid - Retnani Driastuti; Sartika Puspita (Fakultas Kedokteran Gigi Universitas Jember, 2015)
Microhybrid composite resin is the recent development of hybrid composite resin which has a particle size 0,6-0,8 µm and the microfiller size is 0,04 µm. Microhybrid composite resin consist of up to 78% of filler. It increases the mechanical feature of the composite. Bonding is the material that adhere composite resin to email or dentin, in order to reduce the microleakage restoration. The aim of this study was to evaluate the microleakage differences between the fifth generation bonding and seventh generation bonding in fifth class restoration of microhybrid composite resin. It was in vitro experimental laboratories. The samples were post extraction tooth that prepared into fifth class cavity of Black classification. There were two groups, the first group was using fifth bonding generation and the second was seventh bonding generation. Microleakage was measured by observing the penetration of 2% methylen blue through by stereomicroscope. Data were analyzed by Mann-Whitney U. The result showed significant differences of microleakage between groups (p<0,05). This study was concluded that microleakage in seventh bonding generation more common than fifth bonding generation.